A survey on subtypes and clinical characteristics of 1061 patients with urticaria in the primary care institutes in Japan. Issue 12 (26th August 2022) - Saito, Ryo; Takahagi, Shunsuke; Nakano, Fumi; Furutani, Kiyoshi; Mihara, Shoji; Numata, Tsunemi; Kameyoshi, Yoshikazu; Tanaka, Toshihiko; Shindo, Hajime; Niimi, Naomasa; Iwamoto, Kazumasa; Hiragun, Takaaki; et al.
Abstract: The prevalence of urticaria has been reported mostly in Europe and North America. However, precise information regarding its subtypes and clinical characteristics in primary care practice, especially in Asian countries, are scant. Patients with urticaria and/or angioedema who visited nine primary clinics of accredited dermatologists and allergologists in Japan were recruited from October to November 2020. The information of age, sex, disease duration, urticaria control test (UCT), and concomitant urticaria subtypes were collected. A total of 1061 patients participated. The number of patients was high in the 20 to 50 age groups with a peak in the 40s. The most frequent urticaria subtype was chronic spontaneous urticaria (CSU) followed by dermographism, acute spontaneous urticaria (ASU), angioedema, and cholinergic urticaria (CholU) (66.8%, 22.7%, 18.9%, 14.1% and 5.7% in all patients with urticaria). CSU development increased with age from the 20s to 50s, especially in females. Dermographism had a peak in the 40s. ASU had bimodal peaks in childhood and in the 30s. CholU was common in males in the 10–20s. Most angioedema patients were female with an increase in their 30s. Angioedema was solely present in 14 of 1061 participants (1.3%), while 136 (12.8%) had angioedema concomitant with urticaria. UCT showed poorly controlled urticaria with lower scores in patients with concomitant CSU and other subtypes than in those with CSU alone. Urticaria tends to develop in young to middle‐aged females. The most common urticaria subtype is CSU, while the number of patients with CholU is high and that of angioedema is low in Japan.